Changes of brain-derived neurotrophic factor (BDNF) levels after different exercise protocols: a systematic review of clinical studies in Parkinson’s disease - Paterno, Andrea; Polsinelli, Giovanni; Federico, Bruno (Frontiers in Physiology, 2024)
Background: Brain-Derived Neurotrophic Factor (BDNF) serum levels are reduced in patients with Parkinson's Disease (PD).Objectives: This study aimed to assess the effect of exercise intensity, volume and type on BDNF levels in patients with PD.We searched clinicaltrials.gov, CINAHL, Embase, PubMed, Scopus, Web of Science for both controlled and noncontrolled studies in patients with PD, published between 2003 and 2022, which assessed BDNF before and after different exercise protocols. Exercise intensity was estimated using a time-weighted average of Metabolic Equivalent of Task (MET), while exercise volume was estimated by multiplying MET for the duration of exercise. Exercise types were classified as aerobic, resistance, balance and others. We computed two distinct standardized measures of effects: Hedges' g to estimate differences between experimental and control group in pre-post intervention BDNF changes, and Cohen's d to measure prepost intervention changes in BDNF values for each study arm. Meta-regression and linear regression were used to assess whether these effect measures were associated with intensity, volume and type. PROSPERO registration number: CRD42023418629.Results: Sixteen studies (8 two-arm trials and 8 single-arm trials) including 370 patients with PD were eligible for the systematic review. Selected studies had a large variability in terms of population and intervention characteristics. The metaanalysis showed a significant improvement in BDNF levels in the exercise group compared to the control group, Hedges' g = 0.70 (95% CI: 0.03, 1.38), with substantial heterogeneity (I 2 = 76.0%). Between-group differences in intensity were positively associated with change in BDNF in a subset of 5 controlled studies. In the analysis which included non-controlled studies, intensity and total exercise volume were both positively associated with BDNF change. No difference was found according to exercise type.Exercises of greater intensity may increase BDNF levels in patients with PD, while the role of volume of exercise needs to be further explored.